Thyrotoxicosis with concomitant thyroid cancer. Issue 7 (July 2019) - Fu, Hao; Cheng, Lin; Jin, Yuchen; Chen, Libo
Abstract : Thyrotoxicosis with concomitant thyroid cancer is rare and poorly recognized, which may result in delayed diagnosis, inappropriate treatment and even poor prognosis. To provide a comprehensive guidance for clinicians, the etiology, pathogenesis, diagnosis and treatment of this challenging setting were systematically reviewed. According to literatures available, the etiologies of thyrotoxicosis with concomitant thyroid cancer were categorized into Graves' disease with concurrent differentiated thyroid cancer (DTC) or medullary thyroid cancer, Marine–Lenhart Syndrome with coexisting DTC, Plummer's disease with concomitant DTC, amiodarone-induced thyrotoxicosis with concomitant DTC, central hyperthyroidism with coexisting DTC, hyperfunctioning metastases of DTC and others. The underlying causal mechanisms linking thyrotoxicosis and thyroid cancer were elucidated. Medical history, biochemical assessments, radioiodine uptake, anatomic and metabolic imaging and ultrasonography-guided fine-needle aspiration combined with pathological examinations were found to be critical for precise diagnosis. Surgery remains a mainstay in both tumor elimination and control of thyrotoxicosis, while anti-thyroid drugs, beta-blockers, 131 I, glucocorticoids, plasmapheresis, somatostatin analogs, dopamine agonists, radiation therapy, chemotherapy and tyrosine kinase inhibitors should also be appropriately utilized as needed.